Citrus Greening (Huanglongbing): A Serious Threat to the Florida Citrus Industry - Jamie D. Burrow; Megan M. Dewdney; Tripti Vashisth; Lauren M. Diepenbrock (EDIS)
This 2-page trifold brochure is a minor revision written by J. D. Burrow, M. M. Dewdney, T. Vashisth, and L. M. Diepenbrock, and published by the Horticultural Sciences Department, June 2018.